Pengaruh Metode Pembelajaran Luar Kelas Berbasis TGT terhadap Peningkatan Motivasi Belajar IPA-Materi Keanekaragaman Hayati - Haq, Indah Arinal; Hidayat, Muhammad Luthfi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the effect of TGT (Team Games Tournament)-based outdoor learning methods on increasing science learning motivation in class VII students of SMPN 5 Sukoharjo. The research method used is a quasi-experimental with a pre-test post-test control group design. The research sample consisted of two classes, namely the experimental group taught using TGT-based outdoor learning methods. Data were collected through a learning motivation questionnaire using a Likert scale and analyzed using a statistical test in the form of a paired t-test to determine the significance of increasing student learning motivation before and after the application of the learning method. The results showed that (1) the TGT-based outdoor learning method can significantly increase students' science learning motivation, where the pretest score before treatment in VIIC was 3.23 and after treatment increased to 4.14, while the VIIF class before treatment was 3.28 and after treatment increased to 4.26. (2) paired sample t-test statistical test obtained p-value (Sig.) of 0.000 smaller than 0.05, so there is a statistically significant difference between the scores before and after the intervention. Thus, the use of TGT-based outdoor learning methods can be an effective alternative to increase students' learning motivation in science learning, especially in biodiversity material.